EFFECT OF PRE-FERMENTED JUICE, LACTOBACILLUS PLANTARUM AND LACTOBACILLUS BUCHNERI ON THE FERMENTATION CHARACTERISTICS AND AEROBIC STABILITY OF HIGH DRY MATTER ALFALFA BALE SILAGE - F. Koc; S. Ozturk Aksoy; A. Agma Okur; G. Celikyurt; D. Korucu; M. L. Ozduven (Journal of Animal and Plant Sciences, 2017)
The experiment was conducted to investigate the effects of pre-fermented juice (PFJ), Lactobacillus plantarum and Enterococcus faecium (LP), and Lactobacillus buchneri (LB) on the fermentation characteristics and aerobic stability of alfalfa bale silage. The herbage was wilted to 602.3 g/kg dry matter (DM). Treatments of alfalfa silage included (1) control; (2) PFJ: 2.6×105 colony-forming units (cfu/g);  (3) LP: 1.0×106 cfu/g Lactobacillus plantarum and Enterococcus faecium (Pioneer 1188, USA) and (4) LB: 1.0×106 cfu/g Lactobacillus buchneri (Pioneer 11A44) and baled, 150 days. At the end of the ensiling period, three bales of each treatment group were opened, chemical and microbiological analyses were made. Consequently, lactic acid bacteria inoculants and PFJ increased the quality of alfalfa silages. In terms of aerobic stability, PFJ and LP used had a positive effect on CO2 concentrations coliform bacteria and yeast. Also, LB inoculant decreased NDF content and increased in vitro organic matter digestibility of silages. A total number of 15 representatives of lactic acid bacterial strains were retained and among them 3 dominant genus were identified as Lactobacillus plantarum (46.66%), Lactobacillus pentosaceus (33.33%)and Lactobacillus collinoides (20%). It can be concluded that PFJ can be used as silage additive alfalfa bale silage in farm condition.
Keywords: Alfalfa bale silage; identification; in vitro organic matter digestibility; lactic acid bacterial inoculants; PFJ (pre-fermented juice